Developmental endothelial locus 1: the present and future of an endogenous factor in vessels - Jiang, Daisong; Yue, Honghua; Liang, Wei-Tao; Wu, Zhong (Frontiers in Physiology, 2024)
Developmental Endothelial Locus-1 (DEL-1), also known as EGF-like repeat and discoidin I-like domain-3 (EDIL3), is increasingly recognized for its multifaceted roles in immunoregulation and vascular biology. DEL-1 is a protein that is mainly produced by endothelial cells. It interacts with various integrins to regulate the behavior of immune cells, such as preventing unnecessary recruitment and inflammation. DEL-1 also helps in resolving inflammation by promoting efferocytosis, which is the process of clearing apoptotic cells. Its potential as a therapeutic target in immune-mediated blood disorders, cardiovascular diseases, and cancer metastasis has been spotlighted due to its wide-ranging implications in vascular integrity and pathology. However, there are still unanswered questions about DEL-1's precise functions and mechanisms. This review provides a comprehensive examination of DEL-1's activity across different vascular contexts and explores its potential clinical applications. It underscores the need for further research to resolve existing controversies and establish the therapeutic viability of DEL-1 modulation.